An overview on current application of nanofluids in solar thermal collector and its challenges. (January 2016) - Leong, K.Y.; Ong, Hwai Chyuan; Amer, N.H.; Norazrina, M.J.; Risby, M.S.; Ku Ahmad, K.Z.
Abstract: The increase in energy demands and depletion of fossil fuel for power generation are the major concern nowadays. Utilization of renewable energy sources can be regarded as one of the options to tackle these issues. Renewable energy such as solar powered energy can be harnessed by using solar thermal collector. An efficient solar thermal collector must be coupled with fluids which possess superior thermal and optical properties. New generation of heat transfer fluid such as nanofluid is proven to have good prospect to be utilized in the solar collector. Thus, this article reviews the current researches on application of nanofluids in solar collector and probable challenges that might need to be faced in the development of an efficient solar thermal collector with nanofluid.